Migration and human rights: The case of Filipino Muslim women in Sabah, Malaysia - Hilsdon, Anne-Marie (Pergamon, 2006)
From the 1960s Sabah accepted refugees who fled Mindanao after the war escalated against insurgent Muslim groups. From the 1970s, labour migration to Sabah increased exponentially as Filipinos attempted to escape the structural poverty of their country by ameliorating Malaysia's labour shortage in construction, oil palm and service industries. Various tensions developed in Sabah between migrants, and local communities and the state. Migrant Muslim women in particular experienced violence on a number of different fronts: oppression at the level of citizenship, institutions and culture produced physical, economic and social violence which differentiated their lives from those of both Malaysian citizens and Filipinos in the Philippines. The article addresses, through life narratives, the parameters of such violence and women's resilience, invoking questions of who ought to defend and protect the rights of migrant Muslim women.